2021
DOI: 10.1002/mds.28862
|View full text |Cite
|
Sign up to set email alerts
|

Functional Topography of the Human Subthalamic Nucleus: Relevance for Subthalamotomy in Parkinson's Disease

Abstract: Background The subthalamic nucleus (STN) is considered a key structure in motor, behavioral, and emotional control. Although identification of the functional topography of the STN has therapeutic implications in the treatment of the motor features of Parkinson's disease (PD), the details of its functional and somatotopic organization in humans are not well understood. Objective The aim of this study was to characterize the functional organization of the STN and its correlation with the motor outcomes induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 83 publications
(209 reference statements)
0
24
0
Order By: Relevance
“…1b and Supplementary Fig. 1 ), the target of the M1 and SMA 1 , 29 , 30 , 49 , 51 . Together with the motor-related STN activity observed during the reaching task (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1b and Supplementary Fig. 1 ), the target of the M1 and SMA 1 , 29 , 30 , 49 , 51 . Together with the motor-related STN activity observed during the reaching task (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to effectively "steer" the stimulation in specific directions could potentially increase the therapeutic window as well as widen the threshold before inducing side effects (22). In addition, directional leads may also help to optimize the benefit throughout personalized parameters, given that specific "sweet-spot" areas for specific motor and non-motor clinical benefits have been found (23)(24)(25). Computational modeling studies have demonstrated that directional leads may have the capability to steer the center of the VTA up to 1.3 mm (22).…”
Section: Electrodesmentioning
confidence: 99%
“…The preferential target is the sensorimotor portion of the subthalamic nucleus (STN) which is often located within its dorsolateral part (13)(14)(15). Yet, the existence and location of a potential anatomical sweet spot within the STN remains a much debated question (16).…”
Section: Discussionmentioning
confidence: 99%